Application Of Modern Wound Care Using Moist Wound Healing Techniques In Diabetes Mellitus Patients - Rafika Nur Siregar (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Diabetes Mellitus often becomes a serious health problem in various developing and developed countries in the world. Most people with diabetes mellitus are at risk of developing diabetic ulcers. If not treated quickly it can develop into an infection. The newest wound healing methods currently have an important role in treating diabetic ulcers, one of which is Modern Dressing with Moist Wound Healing. The aim of this research is to identify the effectiveness of modern wound care using moist wound healing dressing techniques in healing diabetic ulcers at the Sering Road. The research design used in this study used a quasi-experimental design with a cross- sectional method approach. The sampling used was accidental sampling, namely 30 respondents. Based on the results of the Paired T-Test and Independent T-Test, the p- value was obtained (0.000 < ? 0.05), in the control group, p value ? = 0.080 (p > 0.05). Thus, it can be said that there is no effectiveness of modern wound care using moist wound healing dressing techniques in healing diabetic ulcers at the Sering Road. It is hoped that Sering Road can improve the quality and quality of modern wound care services using moist wound healing dressing techniques for diabetic ulcer sufferers.